Cell and matrix response of temporomandibular cartilage to mechanical loading. Issue 2 (February 2016) - Utreja, A.; Dyment, N.A.; Yadav, S.; Villa, M.M.; Li, Y.; Jiang, X.; Nanda, R.; Rowe, D.W.
Summary: Objectives: The generation of transgenic mice expressing green fluorescent proteins (GFPs) has greatly aided our understanding of the development of connective tissues such as bone and cartilage. Perturbation of a biological system such as the temporomandibular joint (TMJ) within its adaptive remodeling capacity is particularly useful in analyzing cellular lineage progression. The objectives of this study were to determine: (i) if GFP reporters expressed in the TMJ indicate the different stages of cell maturation in fibrocartilage and (ii) how mechanical loading affects cellular response in different regions of the cartilage. Design/methods: Four-week-old transgenic mice harboring combinations of fluorescent reporters (Dkk3-eGFP, Col1a1(3.6 kb)-GFPcyan, Col1a1(3.6 kb)-GFPtpz, Col2a1-GFPcyan, and Col10a1-RFPcherry) were used to analyze the expression pattern of transgenes in the mandibular condylar cartilage (MCC). To study the effect of TMJ loading, animals were subjected to forced mouth opening with custom springs exerting 50 g force for 1 h/day for 5 days. Dynamic mineralization and cellular proliferation (EdU-labeling) were assessed in loaded vs control mice. Results: Dkk3 expression was seen in the superficial zone of the MCC, followed by Col1 in the cartilage zone, Col2 in the prehypertrophic zone, and Col10 in the hypertrophic zone at and below the tidemark. TMJ loading increased expression of the GFP reporters and EdU-labeling of cells in the cartilage, resulting in a thickness increase of all layers of the cartilage. In addition, mineral apposition increased resulting in Col10 expression by unmineralized cells above the tidemark. Conclusion: The TMJ responded to static loading by forming thicker cartilage through adaptive remodeling.